Pengembangan E-LKPD Berbasis Problem Based Learning Berbantuan Liveworksheet pada Materi Hak dan Kewajiban Kelas IV SDN Pejagan 5 - Icha Berliana Putri Maharani; Izzah Fijriyah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by the limited availability of digital teaching materials supporting Pancasila Education learning, particularly on the topic of rights and obligations. In addition, students still experience difficulties in understanding and applying the concepts of rights and obligations in their daily lives. This study aims to develop a Problem-Based Learning (PBL)-based E-LKPD assisted by Liveworksheets that is valid, effective, and attractive for use in Pancasila Education learning for fourth-grade students at SDN Pejagan 5 Bangkalan. This research employed Research and Development (R&D) using the 4D model, which consists of the Define, Design, Develop, and Disseminate stages. The research subjects included material experts, instructional design experts, teaching material experts, and fourth-grade students at SDN Pejagan 5. Data were collected through interviews, observations, questionnaires, and tests. The data were analyzed using both qualitative and quantitative techniques to determine the validity, effectiveness, and attractiveness of the product. The results showed that the developed PBL-based E-LKPD met the “very valid” criteria, with validation percentages of 87.50% from the teaching material expert, 82.50% from the instructional design expert, and 85.00% from the content expert. The product was also declared highly effective, indicated by a 100% classical learning completeness rate and an N-Gain score of 0.80 in the high category. In addition, the product was categorized as “very attractive” based on teacher response (100%) and student responses (93%). Therefore, the Problem-Based Learning (PBL)-based E-LKPD assisted by Liveworksheets on the topic of rights and obligations for fourth-grade students at SDN Pejagan 5 Bangkalan is considered valid, effective, and attractive, and is feasible to be used as a learning material in Pancasila Education.